Wirtschaftspolitik im Wandel : Ordnungsdefizite und Lösungsansätze - Thieme, H. Jörg; Haucap, Justus (Schriften zu Ordnungsfragen der Wirtschaft ;, 2018)
Containing papers from the 50th Radein Research Seminar, this edited volume focuses on regulatory policy issues and dilemmas. Beyond analyzing regulatory policy in various markets, including factor markets for labor and capital and product markets such as health care, energy, and the media, the papers also address broader themes, such the future of Europe and digitization.